PENERAPAN STRATEGI DALAM MENINGKATKAN KEPUASAN KERJA TENAGA PENDIDIK PADA UPT SPF SDI KASSI-KASSI I KECAMATAN RAPPOCINI KOTA MAKASSAR - Puspitasari, Nur Fajriani; Andayaningsih, Sri; Alamsjah, Alamsjah (Yayasan Nuraini Ibrahim Mandiri, 2024)
This research aims to find out how to implement strategies to increase the job satisfaction of teaching staff at UPT SPF SDI Kassi-Kassi I, Rappocini District, Makassar City. This research is descriptive qualitative in nature, trying to describe the research results as they are. Data collection techniques using observation, interviews and documentation. The data obtained is then processed in the form of words or text which is then expressed in descriptive form. The subjects of this research are teaching staff, while the objects of this research are all activities related to implementing strategies to increase job satisfaction of teaching staff at UPT SPF SDI Kassi-Kassi I. The results of this research explain that there are six strategies implemented at UPT SPF SDI Kassi-Kassi I, Rappocini District, Makassar City in increasing the job satisfaction of teaching staff, namely: establishing effective communication between colleagues by communicating all activities that will be held at school, providing opportunities for teachers to take part in training and development, for example bringing in speakers to conduct KKG, reward and appreciation that are given by school principals to teaching staff, conductive working environment conditions characterized by complete learning facilities, but in terms of school security still needed to be improve, paying attention to work-life balance by dividing time so that work demands and personal matters can be carried out well, and finally participation in decision making where teaching staff are always given the opportunity by the school principal to provide input every time a meeting is held. Keywords: Strategy Implementation and Increased Job Satisfaction